Education on Recognizing The Symptom and Treatment of Knee Osteoarthritis at UNS Hospital - Desy Kurniawati Tandiyo (Smart Society, 2024)
Osteoarhritis (OA) is a chronic degenerative disease characterized by wear on the cartilage structure. In UNS hospital, knee OA is ranked as the 2nd largest cases, after low back pain. Misleading beliefs that OA is an incurable, progressive disease that is associated with specific causal factors can lead patients to cut down on physical activities and adapt to restricted lifestyle with less spontaneity, which in many cases results in a great feeling loss and isolation associated with a reduction in social relationship. There is an urgent need to mitigate this negative impact, using proper patient-education strategies to better manage the disease and improve the concordance between patients’ expectations and treatment outcomes. Overall, patient knowledge about the disease is still inadequate. The aim of this study is to increase the knowledge of patients and patients’ caregiver at UNS hospital about symptoms dan treatment of knee OA. The step of this study consisted of preparation, implementation and evaluation. Before giving education, the participants did pre-test, and after education, the participants did post-test, to know the level of participants’ knowledge about the education. There were 22 female (67%) and 11 male (33%) participants. Mean of the level of participants’ knowledge about 5,42 before giving education, and 7,31 after giving education, so there was an enhancement about 1,89. This program ran well. There was an enhancement level of patients’ and caregiver’s knowledge before and after giving education.